Kandungan Pigmen Klorofil, Karotenoid dan Antosianin Daun Caladium - Diah Wulandari Rousdy, Hasidah, Mukarlina (Universitas Tanjungpura, 2017)
Caladium is a family Araceae which has various colors and patterns of leaves. The mechanism of variation of color and pattern on the leaves is caused by the chlorophyll pigment, carotenoid and anthocyanin. Each variation in color and pattern of the leaf has a different anatomical structure. This research aims to find out the differences in the content of the chlorophyll pigment, carotenoid and anthocyanin as well as examine the anatomical structure of the mesophyll in 6 Caladium plants. This research was conducted from January to May 2016. Measurement of chlorophyll, carotenoid and anthocyanin was conducted using a spectrophotometric method while mesophyll tissue anatomy using the method of wet incision preparation. The results showed that the highest chlorophyll content was found in the leaves of C. schomburgkii by 28.508 mg/l, while the highest carotenoid content was found in C. bicolor 1 by 35.780 Î¼mol/g. The highest anthocyanin content was found in C. bicolor cultivar Blaze by 0.057 mg/g. The cross section area of the red, green and white showed a different mesophyll structure. The green area mesophyll tissue differentiates into palisade and spongy tissue containing chlorophyll, while the red and white mostly showed thet mesophyll tissue that did not differentiate into palisade and spongy tissue. The mesophyll cells in the red area contain anthocyanin, and the white area was not pigmented and there was space between the cells among the palisade tissues and between the upper epidermis and mesophyll tissue.